EVALUASI PROGRAM PROMOSI KESEHATAN PHBS PADA TATANAN RUMAH TANGGA DALAM UPAYA PENCEGAHAN DIARE DI KABUPATEN REJANG LEBONG PROVINSI BENGKULU - , harmansyah, Dra. Yayi Suryo Prabandari, M.Si, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: PHBS Programs is one of the main pillars in the Healthy Indonesia and one of the strategies to reduce the burden on the state and society to health financing with the aim of increasing knowledge, awareness, willingness and ability of people to live clean and healthy, including the private sector and the business community to act and actively achieve optimal health status. Objective : To get a description on the evaluation of PHBS health promotion programs in household terms of input, process, and impact in the prevention of diarrhea in Rejang Lebong Bengkulu Province. Methods: The study was a qualitative study with phenomenological approach. This approach is one of the qualitative research. The implementation this research September 2012 to July 2013. Results: Most of the input element in the implementation of the PHBS in preventing diarrhea in Rejang Lebong District, has met the criteria even though there were still many shortcomings, such as the policy and regulations were not accompanied by good operational cooperation across sectors, and across programs, availability of workforce was lacking, organizing still less than optimal as a lack of clear policies and regulations followed in the implementation of this program. The process does not follow the guidelines of Ministry of Health published in 2011, concerning the implementation of PHBS. On impact evaluation, the results showed a fairly good knowledge of PHBS. Conclusion : Policy and regulation influence each step in program of PHBS. At process, execution and planning, less is entangle of society. Program Impact, have happened the increase knowledge and attitude, development of target and staff was short-range reached.